Pengaruh lingkungan pesantren terhadap kedisiplinan siswa kelas X di Madrasah Aliyah Al Maarif Singosari - Nurfadhilah, Rahma Aulia (Maliki Interdisciplinary Journal, 2024)
Rules for student conduct management in the classroom are known as discipline. Public perception of Islamic boarding schools as places where pupils are more prone to engage in anti-school behaviour is on the rise. Based on first observations, it seems that students residing in Islamic boarding schools often arrive late to class, have no need to wear uniforms, and frequently do not use school supplies. Researchers at Madrasah Aliyah Al Maarif Singosari believe that class X pupils' discipline is significantly impacted by the Islamic boarding school setting. The purpose of this study was to examine the impact of Madrasah Aliyah Al Maarif Singosari Islamic boarding school setting on the discipline of class X pupils. A quantitative method of the correlational kind was used by the researcher. A total of thirty-one students from Madrasah Aliyah Miftahul Huda's Xth grade made up the study sample. A questionnaire was used to gather data for this study, which was backed up by documentation and observation. After that, product moment and basic linear regression were used to examine the gathered data. The study's Simple Linear Regression Test yielded a R squared value of0.22, suggesting that student discipline is affected by factors other than the Islamic boarding school environment by 78%, while the environment itself influences it by 22%. Thus, Islamic boarding schools continue to have a negligible impact. Product Moment Correlation Test results showed a significance level of 0.433, which is higher than the threshold of 0.05; consequently, it appears that X, the environment of the Islamic boarding school, does not significantly relate to Y, the discipline of the students.